2003
DOI: 10.1902/jop.2003.74.8.1161
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Porous and Non‐Porous Teflon Membranes Plus a Xenograft in the Treatment of Vertical Osseous Defects: A Clinical Reentry Study

Abstract: Treatment of vertical osseous defects with nonporous or porous polytetrafluoroethylene membranes in combination with a xenograft resulted in statistically significant improvement in open and closed probing measurements, with no significant difference between treatment groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 76 publications
1
26
0
4
Order By: Relevance
“…PepGen/P-15® (Dentsply Friadent Ceramed, Lakewood, CO, USA) has been used in several bone augmentation procedures, such as socket site preservation, (Hahn et al 2003, Tehemar et al 2003 ridge deficiency (Barboza et al 2002), maxillary sinus grafting, , Degidi et al 2004, Gelbart et al 2005, Philippart et al 2005 and periodontal defects (Yukna et al 1998, Walters et al 2003. However, to a large extent, the above data rely on in vitro observations (Qian and Bhatnagar 1996, Bhatnagar et al 1999, Bhatnagar et al 1997 When PepGen/P-15 was examined in surgical fenestrated membrane-protected periodontal defects in dogs (Artzi et al 2006), it proved to be biocompatible and osteoconductive material (Fig.…”
Section: Growth and Differentiation Factors For Alveolar Ridge Augmenmentioning
confidence: 99%
“…PepGen/P-15® (Dentsply Friadent Ceramed, Lakewood, CO, USA) has been used in several bone augmentation procedures, such as socket site preservation, (Hahn et al 2003, Tehemar et al 2003 ridge deficiency (Barboza et al 2002), maxillary sinus grafting, , Degidi et al 2004, Gelbart et al 2005, Philippart et al 2005 and periodontal defects (Yukna et al 1998, Walters et al 2003. However, to a large extent, the above data rely on in vitro observations (Qian and Bhatnagar 1996, Bhatnagar et al 1999, Bhatnagar et al 1997 When PepGen/P-15 was examined in surgical fenestrated membrane-protected periodontal defects in dogs (Artzi et al 2006), it proved to be biocompatible and osteoconductive material (Fig.…”
Section: Growth and Differentiation Factors For Alveolar Ridge Augmenmentioning
confidence: 99%
“…Outras membranas não-absorvíveis também foram estudadas, como membranas de poli-tetrafluoroetileno (PTFE) (WALTERS et al, 2003), silicone (Biobrane®) (WARRER; KARRING, 1992) e celulose (NOVAES JÚNIOR. et al, 1993).…”
Section: Revisãounclassified
“…et al, 1993). Estudos indicam um melhor preenchimento dos defeitos obtidos com o uso de uma membrana não-absorvível (WALTERS et al, 2003). Contudo, este tipo de membrana apresenta algumas desvantagens como: necessidade de segunda intervenção cirúrgica para remoção e elevada taxa de exposição da membrana devido recessão gengival, desconforto para o paciente, elevado custo e infecções pós-operatórias (SIMION et al, 1999).…”
Section: Revisãounclassified
“…This surgical method leads to desirable outcomes in intrabony defects [2][3][4]. Pontoriero et al [5,6] reported that the guided tissue regeneration technique led to new attachments and alveolar bone formation in Class II furcation defects; however, success rates were lower when Class III furcation defects were ≥ 4 mm.…”
Section: Introductionmentioning
confidence: 99%